Variables Affecting the Use of Prescriptive Formulae to Fit Modern Nonlinear Hearing Aids - Kuk, Francis K.; Ludvigsen, Carl (Journal of the American Academy of Audiology, 1999)
It is routine for audiologists to fit nonlinear hearing aids by using one of several current prescriptive formulae. While such an approach might result in acceptable fittings for single-channel analog compression hearing aids, its direct application to fitting current multichannel compression hearing aids may result in less than an optimal fit. In this paper, the effects of filter bandwidth, number of channels, detector type, compression threshold, attack and release times, and distortion on the final output of a nonlinear compression hearing aid are discussed. The subjective results of such effects and its implications on our clinical practice will be explored as well.Abbreviations: CR = compression ratio, CT = compression threshold, DSL (i/o) = Desired Sensation Level (input/output), FFT = Fast Fourier Transform, HA = hearing aid, IHAFF = Independent Hearing Aid Fitting Forum, I/O = input/output, LGOB = Loudness Growth by Octave Band, RMS = root mean square, UCL = uncomfortable listening level, WDRC = wide dynamic range compression
Keywords: Attack and release times; compression thresholds; detectors; distortion; expansion processing; filter bandwidth; filter channels; prescriptive formulae